Analisa Perkerasan Kaku (Rigid Pavement) pada Ruas Jalan Simpang Pudak – Suak Kandis Kabupaten Muaro Jambi - Arman Ismail; Amsori M Das; Ari Setiawan (Jurnal Talenta Sipil, 2022)
The Simpang Pudak road section is a district road that connects Muaro Jambi with Jambi City. This road section is a link to the economic, social and cultural sectors of Muaro Jambi Regency and Jambi City, so that there are also factory vehicles crossing the Simpang Pudak road section, dominated by small and large trucks transporting economic products and other agricultural products. The condition of the Simpang Pudak Road is a flexible pavement that has destroyed its surface to the foundation layer below it. he purpose of this study is to analyze rigid pavement using the 1993 AASHTO method. Planning with a road length of 312.9 m and a width of 7 meters, with a subgrade CBR of 7.3%, with a W18 value in a year of 455,664,051. In this study, the ESAL value in 30 years was 24,814,115,134 ESAL, with a concrete slab thickness of 27.2 cm. With a continuous type of pavement connection with reinforcement with a plate length of 5.5 meters, M10–150 mm wiremesh reinforcement is installed. As well as installed Tie Bar reinforcement 16 mm with a length of 700 mm and a distance of 750 mm. As well as 32 mm Dowel reinforcement with a length of 450 mm and a distance of 300 mm.